Aspectos genotóxicos induzidos por cádmio em Oreochromis niloticus (PISCES: CICHLIDAE) por microscopia de luz e citometria de fluxo - Juliana Moreira Mendonça (2012)
The steady increase of xenobiotics in the environment has been a matter of concern to public health agencies due to social and economic damage caused by its deleterious effects. Genotoxic substances such as cadmium cause cell damage altering their gene expression, generating imperfections in the processes of replication and repair processes. The quantification of the genotoxic effects is considered and excellent marker of exposure. In this work we used the techniques of light microscopy and flow cytometry to assess the erythrocytic morphological abnormalities in nuclei, and the proportions and integrity of populations erythrocytes, granulocytes, and lymphocytes / thrombocytes of tilapia exposed to cadmium. Animals exposed to concentrations of 0.25-, 2.5 mg.L-1 CdCl2.H2O and controls were analyzed for periods of 48, 96 and 144 hours. Our results showed an increase time and dose dependent in the number of cellular alterations, addition to positive correlations between the nuclear morphological abnormalities and cell membrane integrity. The techniques were adequate in the assessment of the changes indicating their applications in environmental monitoring programs